ISHARYŌ AS A WAY TO COMPENSATION FOR MORAL INJURY IN CASE OF DIVORCE IN JAPAN - ŁUKASIEWICZ, Rafał Andrzej (Comparative Legilinguistics, 2019)
The purpose of this article is to present a compensation for moral injury connected with conjugal infidelity in Japanese Law (isharyō). The compensation for moral injury, which is sentenced because of a divorce could be divided into a compensation for mental disorder and a compensation for deprivation of the status in the society. To analyze this issue it is necessary to discuss context of Japanese culture and society. Furthermore, I present statistics which show factors that have influence on the amount of compensation. Finally, there are remarks on comparative law.